Encrypting text data using elliptic curve cryptography - Ali, Abas Abdullahi (2018)
Elliptic curve cryptography has been a hot topic since its birth in 1985. Elliptic curve cryptography has been proven to be secure and requires small key sizes in comparison to the well-known and most used cryptographic algorithms. In this study, a new approach is proposed to enhance the performance of the encryption which means eliminating classic mapping techniques. In this new procedure, the text is converted into its equivalent ASCII values which will serve as a raw data for the Elliptic curve cryptography. This technique boosts the system performance by wiping out the lookup table compared to the current mapping techniques that tend to share the lookup table between the recipient and the sender. Encrypting and decrypting any text that has an equivalent ASCII code is the core principle of this algorithm.